2012
DOI: 10.1002/hipo.22071
|View full text |Cite
|
Sign up to set email alerts
|

Reducing perceptual interference improves visual discrimination in mild cognitive impairment: Implications for a model of perirhinal cortex function

Abstract: ABSTRACT:Memory loss resulting from damage to the medial temporal lobes (MTL) is traditionally considered to reflect damage to a dedicated, exclusive memory system. Recent work, however, has suggested that damage to one MTL structure, the perirhinal cortex (PRC), compromises complex object representations that are necessary for both memory and perception. These representations are thought to be critical in shielding against the interference caused by a stream of visually similar input. In this study, we admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 78 publications
12
64
0
2
Order By: Relevance
“…The observation that top-down feedback from PRC suppressed part-based responses in lower-level visual regions is consistent with a recent series of findings suggesting that the PRC may be critical in resolving perceptual interference (McTighe et al, 2010;Burke et al, 2010;Romberg et al, 2012;Barense et al, 2012;Newsome et al, 2012). For example, patients with PRC damage were impaired at perceptual discrimination under conditions of high visual interference (a series of complex object discriminations for which object parts were repeatedly presented across trials), but performed normally under conditions of low visual interference (fewer object parts repeated across trials) Newsome et al, 2012).…”
Section: Visual Cortex Activationsupporting
confidence: 89%
See 1 more Smart Citation
“…The observation that top-down feedback from PRC suppressed part-based responses in lower-level visual regions is consistent with a recent series of findings suggesting that the PRC may be critical in resolving perceptual interference (McTighe et al, 2010;Burke et al, 2010;Romberg et al, 2012;Barense et al, 2012;Newsome et al, 2012). For example, patients with PRC damage were impaired at perceptual discrimination under conditions of high visual interference (a series of complex object discriminations for which object parts were repeatedly presented across trials), but performed normally under conditions of low visual interference (fewer object parts repeated across trials) Newsome et al, 2012).…”
Section: Visual Cortex Activationsupporting
confidence: 89%
“…For example, patients with PRC damage were impaired at perceptual discrimination under conditions of high visual interference (a series of complex object discriminations for which object parts were repeatedly presented across trials), but performed normally under conditions of low visual interference (fewer object parts repeated across trials) Newsome et al, 2012). These findings suggest that PRC damage rendered these individuals vulnerable to interference from object parts processed by lower-levels in the visual stream.…”
Section: Visual Cortex Activationmentioning
confidence: 93%
“…We could not exclude problems with familiarity assessment as an influencing factor, similarly like the other studies on familiarity cited in this article. We acknowledge that some studies in aMCI reported difficulties with assessing familiarity in these subjects [55] and over-reliance on familiarity as well [56]. However other studies did not find impaired familiarity-based recognition in contrary to impaired recognition based on recollection in MCI subjects, suggesting that recollection and familiarity might be independent processes associated with distinct anatomical substrates [57], [58].…”
Section: Discussionmentioning
confidence: 71%
“…. Our Our Our Our previous work suggests that t previous work suggests that t previous work suggests that t previous work suggests that the memory impaired he memory impaired he memory impaired he memory impaired cases cases cases cases in the present study in the present study in the present study in the present study may be may be may be may be particularly vulnerable to interference from a particularly vulnerable to interference from a particularly vulnerable to interference from a particularly vulnerable to interference from a barrage of visual information barrage of visual information barrage of visual information barrage of visual information (Barense, Groen, et al, 2012;Newsome, et al, 2012) (Barense, Groen, et al, 2012;Newsome, et al, 2012) (Barense, Groen, et al, 2012;Newsome, et al, 2012) (Barense, Groen, et al, 2012;Newsome, et al, 2012). .…”
Section: 2 MCImentioning
confidence: 69%
“…In addition, recent evidence suggests that both MCI patients and MTL amnesics may be disproportionately vulnerable to interference relative to their age-matched counterparts. Indeed, recent work has shown that removing irrelevant visual information altogether improves performance on memory tasks (Dewar, Alber, Cowan, & Della Sala, 2014;Dewar, Della Sala, Beschin, & Cowan, 2010;Dewar, Garcia, Cowan, & Della Sala, 2009;Dewar, Hoefeijzers, Zeman, Butler, & Della Sala, 2015), as well as perceptual discrimination tasks (Barense, Groen, et al, 2012;Newsome, Duarte, & Barense, 2012). Thus, to the extent that MCI patients and MTL amnesia cases can use spatial information from the retrocue to reduce interference from irrelevant items, it may disproportionately benefit their performance relative to that observed in agematched controls.…”
Section: --------------------------------------Figure 1 About Here --mentioning
confidence: 91%